Research on the Path of Patriotic Education for College Students in the New Era (Asian Education Studies, 2021)
Patriotic education in the new era needs to give full play to the role of the main channel of ideological and political courses, strengthen and improve the ideological and political work team, strengthen the construction of practical education base. At the same time, we will continue to explore new channels for educating people, and will fully integrate patriotic education with cultural and moral education. Students need to strengthen their ideals and beliefs, cultivate their patriotism, and turn their patriotism into a trip to serve the country.